Hadith Life and Power Relations in the Ro'an Tradition at Miftahul Huda Rawalo Banyumas Islamic Boarding School - Mahfudz Al Faozi; Imam Ma’arif Hidayat; Imam Alfi (STIT Sunan Giri Bima, 2025)
This study examines the Ro’an (community service) tradition in Islamic boarding schools as both a manifestation of Living Hadith values such as ta’awun (mutual help), sincerity, and thaharah (cleanliness) and as an arena of power relations among kiai, ustaz, and students. In the digital era, this noble practice faces the risk of meaning distortion and accusations of exploitation on social media, necessitating deeper academic analysis. Using a qualitative case study approach at Miftahul Huda Rawalo Banyumas Islamic Boarding School, data were collected through participatory observation, in-depth interviews, and documentation involving 58 purposively selected participants, consisting of active students and alumni. The two-month fieldwork generated rich textual and observational data, analyzed through stages of data reduction, presentation, and conclusion drawing to identify patterns of meaning and power relations in the Ro’an tradition. The findings reveal that Ro’an serves as an effective medium for internalizing Living Hadith values, fostering spirituality, collective identity, and social discipline among students. However, it also reflects asymmetrical power structures in which institutional authority reinforces obedience and piety through disciplinary mechanisms. The study contributes theoretically by integrating Living Hadith perspectives with Foucault’s concept of power relations, offering insights into how Islamic boarding schools can sustain Ro’an through more humanistic and participatory frameworks in the digital age.